Optimal design of a stair-climbing mobile robot with flip mechanism. (19th March 2018) - Liu, Pengzhan; Wang, Jianzhong; Wang, Xin; Zhao, Peng
Abstract: Stairs overcoming is a primary challenge for mobile robots moving in human environments, and the contradiction between the portability and the adaptability of stair climbing robot is not well resolved. In this paper, we present an optimal design of a flip-type mobile robot in order to improve the adaptability as well as stability while climbing stairs. The kinematic constraints on the flip mechanism are derived to prevent undesired interferences among stairs, wheels and main body during climbing stairs. The objective function is proposed according to the traction demand of the robot during stair-climbing motion for the first time and the value of the objective function is calculated though kinetic analysis. The Taguchi method is using as the optimization tool because of its simplicity and cost-effectiveness both in formulating an objective function and in satisfying multiple constraints simultaneously. The performance of the robot under the optimal parameters is verified through simulations and experiments. Abstract :